Application of AI technique for optimal location of TCSC device - Mohd Daim, Mohd Diah (2010)
This project is about how was to develop dc power supply using the applications of power electronic. In the power generation of most of electrical circuit, dc power supply is very required and demanded. It is familiarly to provide power for control and drive circuit within the main switchmode unit. Depending on the approaching of circuit design, the power supply will be common to either input or output of the circuit modeling. The design of DC power supply depends on the output of circuit design either single output or multiple output. There are different analysis to design the circuit based on the number of output. In this project, there are many applications of power electronics are applied such as transformer, AC to DC converter or rectifier, DC-DC converter, and semicondutor devices like power transistor. The circuit design approaching depends on the combination of these power electronic applications. The power supply designed is fully conversant with various combinations and its designer should be having capability to select the most appropriate for a particular application has indeed very powerful design tools